2019
DOI: 10.1088/1757-899x/702/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Electro-oxidation of renewable glycerol to value added chemicals over phosphorous-doped Pt/MCNTs nanoparticles

Abstract: In the present work, Pt/MCNTs and P-dopedPt/MCNTs catalysts were synthesized via hydrothermal method and utilized for glycerol oxidation reaction (GOR). The catalysts were physio-chemically characterized by Brunauer-Emmett-Teller (BET), X-ray diffraction, field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) to investigate pore size, pore volume, structure and morphology of the catalysts. A remarkable reduction in BET surface area was found for P-dopedPt/MNCTs which 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…46 Several other studies performed at 0.5-1.0 M KOH have shown that Pt is highly selective toward the formation of TA. 98,142,143 In the case of Pt/CNT in 0.5 M KOH at 0.7 V vs RHE, up to 75-95% TA was found over a 2 hour time frame, 142 while over a P-doped Pt/MWCNT catalyst in 0.5 M KOH at 0.73 V, near equimolar amounts of TA and GLA were detected, both accounting for 90% of the final products. 143 These results show that dicarboxylic acids (TA) are only produced under highly alkaline conditions, as was also shown for Au electrodes at pH ≥ 14.3.…”
Section: Pt-based Electrocatalystsmentioning
confidence: 96%
See 4 more Smart Citations
“…46 Several other studies performed at 0.5-1.0 M KOH have shown that Pt is highly selective toward the formation of TA. 98,142,143 In the case of Pt/CNT in 0.5 M KOH at 0.7 V vs RHE, up to 75-95% TA was found over a 2 hour time frame, 142 while over a P-doped Pt/MWCNT catalyst in 0.5 M KOH at 0.73 V, near equimolar amounts of TA and GLA were detected, both accounting for 90% of the final products. 143 These results show that dicarboxylic acids (TA) are only produced under highly alkaline conditions, as was also shown for Au electrodes at pH ≥ 14.3.…”
Section: Pt-based Electrocatalystsmentioning
confidence: 96%
“…98,142,143 In the case of Pt/CNT in 0.5 M KOH at 0.7 V vs RHE, up to 75-95% TA was found over a 2 hour time frame, 142 while over a P-doped Pt/MWCNT catalyst in 0.5 M KOH at 0.73 V, near equimolar amounts of TA and GLA were detected, both accounting for 90% of the final products. 143 These results show that dicarboxylic acids (TA) are only produced under highly alkaline conditions, as was also shown for Au electrodes at pH ≥ 14.3. 90,92 At 1.0 M KOH, Ferreira et al showed for a Pt/C catalyst that higher current densities (90 mA cm -2 ) and hence higher overpotentials, promoted C-C cleavage reactions, whereas lower current densities (60 mA cm -2 ) and overpotentials promoted the formation of TA and reduced the C-C cleavage.…”
Section: Pt-based Electrocatalystsmentioning
confidence: 96%
See 3 more Smart Citations